Religious dimensions of Malaysia’s wellbeing indexes - Ahmad Sarkawi, Azila; Abdullah, Alias; Md. Dali, Norimah (Asia Pacific Institute of Advanced Research, 2017)
Amongst the 57 members of the Organisation of the Islamic Conference’s (OIC) countries, Malaysia is at number one rating in the Islamicity Index, Islamic Index of Wellbeing and Global Muslim Travel Index studies. The rating gave the impression of the liveability or wellbeing in Malaysia within the Islamic sphere. This recognition prompts the study on the indicators of wellbeing that Malaysia has focused on Islamic dimensions. Consequently, content analysis was done on six selected government documents namely the Malaysian Wellbeing Index, the Malaysian Family Wellbeing Index, the Malaysian Urban-Rural National Indicators Network for Sustainable Development, the Malaysian Shariah Index, the Malaysian Ummah Development Index and the Muslim Religiosity and Personality Indexing. The study found that the first three documents embodied indirect religious dimensions in their wellbeing indexing while the latter three have direct religious dimensions. The incorporation of the religious dimensions into the Malaysia’s wellbeing indexing either directly or indirectly shows the relevancy of the religious factor to human wellbeing. Noticeably, the indicators promulgated under each study are organizationally-driven aiming at attaining their specific objectives that invariably led to variations amongst the agencies. Nonetheless, religion has been found to command a significant factor in the wellbeing of Malaysian though different indicators have been used by the six organizations to arrive at this fact.